“The Continuous Restart”: Case Study on Young Adults in Societies in Fast Transition - António Fragoso; Emilio Lucio-Villegas (Adult Education Research Conference, 2004)
In this paper we reflect upon the role of young adults in local development processes in social contexts characterised by strong transition trends. The analysis of two sequentially different generations gives us important elements to arrive at some conclusions about social change, according to the theoretical framework we use.